Impact of Maternal Intake of Artificial Sweetener, Acesulfame-K, on Metabolic and Reproductive Health Outcomes in Male and Female Mouse Offspring - Bridge-Comer, Pania E.; Vickers, Mark H.; Morton-Jones, Jacob; Spada, Ana; Rong, Jing; Reynolds, Clare M. (Frontiers in Nutrition, 2021)
Guidelines advising pregnant women to avoid food and beverages with high fat and sugar have led to an increase in consumption of “diet” options sweetened by artificial sweeteners (AS). Yet, there is limited information regarding the impact of AS intake during pregnancy on the long-term risk of cardio-metabolic and reproductive complications in adult offspring. This study examined the influence of maternal acesulfame-k (Ace-K) and fructose consumption on offspring metabolic and reproductive outcomes. Pregnant C57BL/6 mice received standard chow ad-libitum with either water (CD), fructose (Fr;20% kcal intake), or AS (AS;12.5mM Ace-K) throughout pregnancy and lactation (n=8/group). Postweaning offspring were maintained on a CD diet for the remainder of the experiment. Body weight, food and water intakes were measured weekly. Oral glucose tolerance tests (OGTT) were undertaken at 12 weeks and offspring culled at week 14. Female but not male AS groups exhibited decreased glucose tolerance compared to Fr. There was an increase in gonadal fat adipocyte size in male offspring from AS and Fr compared to CD groups. In female offspring adipocyte size was increased in the Fr compared to the CD group. In female, but not male offspring, there was a trend towards increase in Fasn gene expression in AS compared to the CD group. Maternal AS and Fr also negatively impacted upon female offspring estrus cycles and induced alterations to markers associated with ovulation. In summary, exposure to Ace-k via the maternal diet leads to impaired glucose tolerance and impacts adipocyte size in a sex-specific manner as well as significantly affecting estrus cycles and related gene markers in female offspring. This has implications in terms of providing tailored dietary advice for pregnant women and highlights the potential negative influence of artificial sweetener intake in the context of intergenerational impacts.